Optical Properties of Nanostructures - Fu, Ying; Qiu, Min (Singapore : Pan Stanford, 2011)
This book discusses electrons and photons in and through nanostructures by the first-principles quantum mechanical theories and fundamental concepts (a unified coverage of nanostructured electronic and optical components) behind nanoelectronics and optoelectronics, the material basis, physical phenomena, device physics, as well as designs and applications. The combination of viewpoints presented in the book can help foster further research and cross-disciplinary interaction needed to surmount the barriers facing future generations of technology design.
Includes References 273-282p.; Index 283-288p.
Keywords: Nano structures; Optoelectronics; Nano science